Pengaruh Kompetensi Aparatur Pemerintah Daerah Dan Ketaatan Pada Peraturan Perundangan Terhadap Akuntabilitas Kinerja Instansi Pemerintah Daerah Kabupaten Kerinci - Zachari Abdallah (Economac: Jurnal Ilmiah Ilmu Ekonomi, 2018)
Abstrak : Influence of interest aparatur local government and adherence [at] regulation perundanagn to akuntabilitas governmental institution performance sub-province kerinci. Research this in do [at] 43 SKPD government of sub-province kerinci. Research this use Descriptive method with approach survey. Data collecting of primary in do with give kuesioner to responder head Set of Kerja,bagian keuangan,dan part of perencanaan/program. Result of research show that: first, in parsial and in simultan interest aparatur area and adherence [at] regulation perundangan influential to akuntabilitas performance of institution local government. Both, big its influence of interest aparatur area 31,7% and adherence [at] regulation perundangan to akuntabilitas governmental institution performance equal to 38,1% Third, from both variable the which most dominant influence akuntabilitas governmental institution performance is variable adherence [at] regulation perundangan the big its influence equal to 38,1%. Kata Kunci : interest Aparatur local government, applying Akuntabilitas Monetary, adherence [at] regulation perundangan,akuntabilitas governmental institution performance